PROSPEK EKOSIDA SEBAGAI PELANGGARAN BERAT HAK ASASI MANUSIA DI INDONESIA - Wibowo, Shannon Lorelei; Savitri, Niken (Faculty of Law, Parahyangan Catholic University, 2025)
Ecocide constitutes a major environmental crime driven by power dynamics and carries significant consequences for human life. In the Indonesian context, several environmental incidents, such as river pollution by palm oil industries, the Lapindo mudflow disaster, and gold mining operations in Intan Jaya, Papua, demonstrate the severe and direct impact of environmental harm on communities. This research explores whether such cases in Indonesia can be classified as ecocide and examines whether ecocide should be treated as a serious human rights violation or recognized as a distinct criminal offense. Utilizing a normative-empirical juridical approach, the study concludes that environmental crimes in Indonesia have the potential to be categorized as ecocide and, thus, may qualify as gross human rights violations. Accordingly, two possible regulatory paths are proposed: first, the urgency of ratifying the Rome Statute, should ecocide be included under its jurisdiction as a gross human rights violation; and second, the incorporation of ecocide into Indonesia’s Human Rights Court Law, acknowledging both the potential benefits and challenges of such a legal reform.